Advances in salinity tolerance of soybean: Genetic diversity, heredity, and gene identification contribute to improving salinity tolerance - Hua-tao CHEN; Xiao-qing LIU; Hong-mei ZHANG; Xing-xing YUAN; He-ping GU; Xiao-yan CUI; Xin CHEN (Journal of Integrative Agriculture, 2018)
Salt stress is one of the major abiotic stresses affecting soybean growth. Genetic improvement for salt tolerance is an effective way to protect soybean yield under salt stress conditions. Successful improvement of salt tolerance in soybean relies on identifying genetic variation that confers tolerance in soybean germplasm and subsequently incorporating these genetic resources into cultivars. In this review, we summarize the progress in genetic diversity and genetics of salt tolerance in soybean, which includes identifying genetic diversity for salt tolerant germplasm; mapping QTLs conferring salt tolerance; map-based cloning; and conducting genome-wide association study (GWAS) analysis in soybean. Future research avenues are also discussed, including high throughput phenotyping technology, the CRISPR/Cas9 Genome-Editing System, and genomic selection technology for molecular breeding of salt tolerance.